Language and Citizenship in Japan. - Gottlieb, Nanette (Routledge studies in sociolinguistics., 2012)
The relationship between language and citizenship in Japan has traditionally been regarded as a fixed tripartite: 'Japanese citizenship' means 'Japanese ethnicity, ' which in turn means 'Japanese as one's first language.' Historically, most non-Japanese who have chosen to take out citizenship have been members of the 'oldcomer' Chinese and Korean communities, born and raised in Japan. But this is changing: the last three decades have seen an influx of 'newcomer' economic migrants from a wide range of countries, many of whom choose to stay. The likelihood that they will apply for citizenship.